Geometric structural insights for enhanced radiative efficiency: Spiro[fluorene–carbazole]‐based ortho‐carboranyl luminophores. (9th May 2022) - Ryu, Chan Hee; Lee, Seok Ho; Kim, Mingi; Lee, Kang Mun
Abstract: We herein report the preparation of two compounds (C1 and C2 ) with an ortho ‐carborane cage appended at the C4‐position of the fluorene (C1 ) or carbazole (C2 ) moiety of their spiro[fluorene–carbazole] scaffolds. Photoluminescence spectra of both compounds in solution at 298 K did not demonstrate any emissive trace; however, those of both compounds in solution at 77 K and in the film state exhibited strong orange emission. Interestingly, the quantum efficiency and radiative decay constant of C2 in the film state were much higher than that of C1 . This distinctly showed that the position of the o ‐carborane unit on the scaffold strongly affected the efficiency of the radiative decay process based on intramolecular charge transfer (ICT) transitions. These findings revealed that that the electronic environment of the scaffold‐molecule linked with the o ‐carborane cage plays an important role to control the ICT‐based radiative decay process. Abstract : The distinct difference in solid‐state emission efficiency between two spiro[fluorene–carbazole]–bearing o ‐carboranyl luminophores showed that the electronic environment of the scaffold moiety the o ‐carborane cage is attached can significantly affect controlling intramolecular charge transfer‐based radiative decay.